PENDEKATAN EKONOMI DALAM PENGEMBANGAN SUATU METODOLOGI UNTUK PERKEBUNAN ENERGI PADA LAHAN KRITIS DI PULAU JAWA - Suarna, Endang (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
As a result of population pressure, deforestation in Java has increasedconsiderably that causes an increase on critical land. The situation is worsened by increasing of kerosene and diesel prices that causes to an increase on fuelwood utilization that would lead to increase of illegal cutting. The increase of critical land could lead to increase of soil erosion, landslide, and flood as a result of a reduction in water absorption and soil retention. The Department of Forestry has initiated a reforestation program to ameliorate the situation. However, as the limited budget, the economics of the program needs to be examined further. Based on benefit-cost ratios, economic contributions of the fuelwood component indicated that the reforestation program or energy plantation was economically unfeasible. However, by including benefits of soil erosion control the program waseconomically attractive on some sites. A methodology was developed to prioritize which critical land to reforest. This was applied by identifying market price of fuelwood at minimum yield that would justify an energy plantation investment. The method indicated that subject to budget availability, critical lands should be reforested in descending order of productive potential until the site of minimum yields is reached.